2008
DOI: 10.1377/hlthaff.27.1.256
|View full text |Cite
|
Sign up to set email alerts
|

Using An Economic Model Of Diabetes To Evaluate Prevention And Care Strategies In Australia

Abstract: The health benefits and costs of a national diabetes screening and prevention scenario are estimated among Australians ages 45-74. The Australian Diabetes Cost-Benefit Model is used to compare baseline and scenario outcomes from 2000 to 2010. Those newly diagnosed in 2000 receive intensive care, resulting in lower complication rates. People "at high risk" of developing diabetes are offered lifestyle intervention, reducing the numbers developing diabetes. A total of 115,000 people became "newly diagnosed." Amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 8 publications
0
40
0
Order By: Relevance
“…The costs may not be applicable to the UK but the relativities are. Colagiuri et al (2008) 139 modelled screening at different ages in a complex model with 15 diabetes states, ranging from no diabetes and low risk of future diabetes, through no diabetes but high risk, to diabetes and early complications, and, finally, to diabetes with late complications and then death. Screening was carried out in three stages: risk scoring; FPG in high risk; and OGTT for borderline FPGs.…”
Section: Review Of Cost-effectiveness Studiesmentioning
confidence: 99%
“…The costs may not be applicable to the UK but the relativities are. Colagiuri et al (2008) 139 modelled screening at different ages in a complex model with 15 diabetes states, ranging from no diabetes and low risk of future diabetes, through no diabetes but high risk, to diabetes and early complications, and, finally, to diabetes with late complications and then death. Screening was carried out in three stages: risk scoring; FPG in high risk; and OGTT for borderline FPGs.…”
Section: Review Of Cost-effectiveness Studiesmentioning
confidence: 99%
“…The cost-effectiveness of lifestyle interventions has been examined in a number of clinical trials and computer modelling simulations. Although pharmacological interventions have also been shown to prevent diabetes, the cost effectiveness and risk-benefit ratio are less clear [32][33][34][53][54][55][56][57][58][59][60][61][62][63].…”
Section: Cost-effectiveness Of Diabetes Preventionmentioning
confidence: 99%
“…Short time-horizon studies have shown prediabetes lifestyle interventions to be cost-effective and even cost saving. Long time-horizon studies based on 10 to 30 year predictive mathematical models have used different models with different data, and have come to different conclusions about the cost-effectiveness of prediabetes lifestyle interventions [54][55][56][68][69][70][71][72][73][74][75][76][77]. Predictive models are useful, but they also have limitations.…”
Section: Cost-effectiveness Of Diabetes Preventionmentioning
confidence: 99%
“…Reducing the onset of diabetes could have beneficial impacts on overall population health and on the economic burden of healthcare. A number of studies have evaluated the cost-effectiveness of diabetes prevention, with two recent ones evaluating a range of screening and treatment programmes [6,7]. The study by Gillies et al [7] evaluated lifestyle interventions and combined pharmacotherapies in the UK population.…”
Section: Introductionmentioning
confidence: 99%
“…The study by Gillies et al [7] evaluated lifestyle interventions and combined pharmacotherapies in the UK population. The Colagiuri study was undertaken in the Australian population, but analysed a lifestyle intervention only [6]. No study has yet compared individual pharmacotherapies with different lifestyle interventions in an Australian population.…”
Section: Introductionmentioning
confidence: 99%